LINGUISTIC FEATURES OF PHRASEOLOGICAL UNITS RELATED TO THE FIELD OF ECONOMICS IN THE ENGLISH AND UZBEK LANGUAGES - Muxiddinova Hilola (TADQIQOTLAR, 2025)
Abstract:  Phraseological  units  represent  an  important  layer  of  language  that reflects both linguistic structure and cultural worldview, playing a significant role in the expression of abstract concepts in specialized fields such as economics. This article explores the linguistic features of phraseological units related to the field of economics in  the  English  and  Uzbek  languages,  with  the  aim  of  identifying  their  structural, semantic, and functional characteristics. Economic phraseology is of particular interest due to its metaphorical nature and its widespread use in professional discourse, media texts,  and  everyday  communication.  The  study  applies  descriptive  and  contrastive methods  to  analyze  economic  phraseological  units  selected  from  dictionaries, economic  texts,  and  media  sources.  Special  attention  is  paid  to  their  semantic motivation, metaphorical foundations, and degree of idiomaticity. The analysis reveals that  many  economic  phraseological units  in  both languages  are  based on  universal conceptual  metaphors  such  as  economy  as  movement,  struggle,  growth,  and mechanism, while others reflect culture-specific images and national experience.